Tasty Catering : building the brand - Thompson, Kenneth R., (SAGE business cases., 2023)
Tasty Catering started as a hot dog stand in 1984. By 2008, it had blossomed into a catering company with over 10,000 annual catering events and 200 employees. This success occurred by analyzing and understanding the market and having the skills, persistence, and careful management to meet changing customer requirements.This case reviews the history of Tasty Catering, its focus on product quality, and services to the client. The company has created a culture that focuses on the employees as the essential link in delivering quality. In addition, the organization has developed a strong operational mantra to specifically understand the requirements of the customer, and embed in each employee the desire to meet and exceed those customer requirements.At the end of the case, students will advise the owners where to expand their business further: corporate accounts, wedding catering, or selling large contracts of cookies or muffins to major corporate or government clients (school districts, airlines).